Pengaruh Penggunaan Fitur Shopee Games terhadap Customer Engagement pada Kalangan Mahasiswa di Kota Malang - Molyo, Priyo Dari; Yulistiowati, Irma Mufita; Zulhilmi, Fajar (Universitas Merdeka Malang, 2021)
In the midst of the increasing number of people to fulfill their needs by shopping online, there are dozens of e-commerce providers that offer the same service, namely accommodating sellers to be able to sell online, this is a challenge for e-commerce players to scramble for attention so that consumers choose e- commerce as a